Electrokinetically modulated flow of couple stress magneto‐nanofluids in a microfluidic channel. Issue 1 (17th October 2018) - Ramesh, K.; Kumar, Deepak; Devakar, M.
Abstract: In the present article, the theoretical investigation is presented for the mixed electrokinetic and pressure‐driven transport of couple stress nanoliquids in a microchannel with the effect of magnetic field and porous medium. This topic has gained a remarkable scope in nanoscale electro‐osmotic devices. The formulation of the present mathematical problem is simplified using the Debye‐Hückel linearization assumption. The merging model has important features such as the thermal Grashof number, solutal Grashof number, Joule heating, Helmholtz‐Smoluchowski velocity. The analytical solutions are presented for the axial velocity, temperature, and solute concentration. The expressions for the heat transfer rate, solute mass transfer rate, and surface shear stress function at the walls are also presented. The results display that, the velocity of the couple stress nanofluid is less in the case of pure electro‐osmotic flow as compared to that of combined electro‐osmotic and pressure‐driven flow. When the Joule heating parameter vanishes, the temperature and solute concentration profiles are linear, otherwise nonlinear. The shear stress function is larger in the case of pure electro‐osmotic flow and it is smaller for the combined effects of electro‐osmotic and pressure gradient. The present analysis places a significant observation that the various zeta potential plays an influential role in heartening fluid velocity. The analysis is relevant to electrokinetic hemodynamics and microfluidics.